Eksplorasi benih Jati Putih (Gmelina arborea Roxb) dari berbagai variasi habitat untuk populasi pemuliaan - Dedi Setiadi; Hamdan Adma Adinugraha (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
White teak (Gmelina arborea Roxb) is one of the types developed for the development of plantations, this species is an exotic tree that grows quickly, the planting technique is not difficult and has a good economic value. The wood is used for various purposes, especially for the manufacture of construction materials, carpentry, plywood, matches, containers and other wood craft materials. One aspect that determines the success of plantation development is the availability of seeds, especially quality seeds that are superior genetically, physically and physiologically, available in sufficient quantities, on time and have the ability to adapt to the environment in which they grow. The development of this plant needs to be accompanied by a breeding program, one of the forest plant breeding activities is exploration. Exploration activities of a type of plant in its natural habitat are important to support research and development activities of an institution and to meet market needs for these seeds. The purpose of seed exploration is to get white Teak seeds that represent a variety of habitats to support breeding activities. Exploration of white teak seeds is carried out in Kalianda (South Lampung), Bondowoso (East Java), Bantul (Yogyakarta), Parung Panjang (West Java) and Lombok (West Nusa Tenggara). The results of the exploration obtained 108 mother trees from Kalianda 25 mother trees with seed size (18.32 mm; 10.25 mm), Bondowoso 30 mother trees (17.78 mm; 9.64 mm), Bantul 21 mother trees (19, 24 mm; 11.40 mm), Parung length 15 mother trees (19.41 mm; 9.42 mm) and Lombok 17 mother trees (18.58 mm; 10, 31 mm).